1999
DOI: 10.5694/j.1326-5377.1999.tb127675.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with New South Wales methadone programs in 1994: lives lost and saved

Abstract: Objectives To estimate the effects of methadone programs in New South Wales on mortality. Design and cases Retrospective, cross‐sectional study of all 1994 New South Wales coronial cases in which methadone was detected in postmortem specimens taken from the deceased. Cases were people we identified as patients in NSW methadone maintenance programs or those whose deaths involved methadone syrup diverted from maintenance programs. Outcome measures Relative risks of fatal, accidental drug toxicity in the first tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 19 publications
4
77
1
3
Order By: Relevance
“…Furthermore, with long half-life drugs such as methadone significant risks are associated with drug accumulation from one dose to the next. This has led to a substantial increase in mortality both on the street and in methadone maintenance programs [164][165][166][167].…”
Section: Heroin and Other Opioidsmentioning
confidence: 99%
“…Furthermore, with long half-life drugs such as methadone significant risks are associated with drug accumulation from one dose to the next. This has led to a substantial increase in mortality both on the street and in methadone maintenance programs [164][165][166][167].…”
Section: Heroin and Other Opioidsmentioning
confidence: 99%
“…Drug-related deaths are common among patients on methadone therapy, as are other medical causes and trauma (Clausen, Waal, Thoresen, & Gossop, 2009;Zador & Sunjic, 2000). Individuals on methadone therapy have a higher risk of death during periods of induction and discontinuation (Caplehorn & Drummer, 1999;Clausen et al, 2009;Degenhardt et al, 2009;Srivastava & Kahan, 2006;Zador & Sunjic, 2000;Zanis & Woody, 1998). Additionally, some evidence suggests an association between drug-related death and psychiatric disorders, during or after cessation of methadone treatment (Cousins et al, 2011;Zanis & Woody, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The deaths are mostly due to respiratory arrest and very often occur during sleep when breathing is primarily regulated by automatic neurochemical control [81,82]. This has prompted clinical research on the effects of narcotic drugs on breathing during sleep [83].…”
Section: Sleep Apnoea and Substance Abusementioning
confidence: 99%
“…In contrast, acute narcotic use is often fatal. Australian data showed that the relative risk of fatal accidental drug toxicity for patients in the first 2 weeks of methadone maintenance was 6.7 times that of heroin addicts not in the treatment programme and 97.8 times that of patients who had been on maintenance for more than 2 weeks [81]. The immediate cause of death is often pulmonary oedema secondary to prolonged hypoventilation [81,82].…”
Section: Sleep Apnoea and Substance Abusementioning
confidence: 99%
See 1 more Smart Citation